The influence of microblogging on personal public participation - Ruixia Han (2010 IEEE 2nd Symposium on Web Society, 2010)
This essay examines the influence of microblogging on personal public participation by articulating microblog with media event. Based on analyzing of microblogging characters, the paper thinks web-identity connected with roles in microblog tenders to evoke media event which is different from media event evoked by mainstream media. Further, by articulating hegemony of Hall, ritual view of communication of James Carey with media event evoked by microblogger, the paper insists microblogging would enhance personal public participation. At the last, the essay analyzes the possible danger that microblogging would face.